MENTOR AND THE ROLE IN SUPPORTING FUTURE TEACHERS DURING PEDAGOGICAL PRACTICE IN GENERAL SECONDARY EDUCATION INSTITUTIONS - Палагута, Ілона (Modern engineering and innovative technologies, 2024)
The article summarizes the concept of “mentoring” and its role in future teachers’ pedagogical practice in general secondary educational institutions. The main models of future teachers’ training in higher educational institutions are presented. The main